ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MATERI BILANGAN PADA ANAK JALANAN DI KELAS BINAAN ADIYAKSA KOTA MAKASSAR - Lisnasari Andi Mattoliang; Wulandari Ningsih; Ulfiani Rahman; A. Sriyanti; Munirah (Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to determine the ability to understand mathematical concepts and to determine the inhibiting factors of street children in completing the ability test for understanding mathematical concepts in number operations material. This study uses a qualitative method by selecting several informants who are street children from the Adiyaksa Development Class. Data collection was done by giving the informant a concept understanding ability test, and interviews. The data were analyzed by being reduced, then presented and then drawing conclusions. The results of the study based on the test results of 5 student respondents, it was found that respondents coded 01 and 05 got a score of 100. These results indicate that the two students have understood the material for number operations well. However, the other three respondents, namely respondents coded 02 and 03 each with a test score of 60 and respondents coded 04 obtained a test result of 80. Based on the results of interviews with the three respondents, it was found that they had difficulty performing number operations on numbers big. The inhibiting factors for the ability to understand the concept of number operation material in street children in the Adiyaksa fostered class Makassar are 1) the unavailability of learning media in the form of counting aids, 2) the busyness of students as street children, namely helping their parents in earning a living, and 3) lack of schedule for math subjects.